Spawning frequency of Sardina pilchardus, (Walb.) off the Spanish North Atlantic coast in 1997 - Quintanilla-Hervás, Luis Francisco; Pérez-Contreras, María Nélida (Fisheries Research, 2000)
This paper presents the spawning fraction and spawning frequency estimates of Sardina pilchardus off the North Atlantic Spanish coast in March 1997 using the Postovulatory Follicle Method. The fraction of mature female sardine with less than 48-h-old postovulatory follicles averaged 0.18 (standard deviation = 0.08), indicating that the mean interval between each spawning was approximately six days along the eastern Cantabrian coast. This spawning fraction estimate is higher than those estimated for the western Cantabrian and Galicia coasts as could be expected from the differential distribution of sardine by age with an increment towards the east; and it is slightly lower than in previous years due to changes in the species distribution pattern by age. SI